Existence and nonexistence of positive solutions for a class of third order BVP with integral boundary conditions in Banach spaces - Zhao, Junfang; Wang, Peiguang; Ge, Weigao (Communications in nonlinear science & numerical simulation, 2011)
This paper investigates the existence, nonexistence, and multiplicity of positive solutions for a class of nonlinear boundary-value problems of third order differential equations with integral boundary conditions in ordered Banach spaces by means of fixed-point principle in cone and the fixed-point index theory for strict set contraction operator. In addition, an example is worked out to demonstrate the main results.